Clinical and immunological spectra of human cutaneous leishmaniasis in North Africa and French Guiana - Saidi, Nasreddine; Blaizot, Romain; Prévot, Ghislaine; Aoun, Karim; Demar, Magalie; Cazenave, Pierre André; Bouratbine, Aida; Pied, Sylviane (Frontiers in Immunology, 2023)
Cutaneous leishmaniasis (CL) caused by infection with the parasite Leishmania exhibits a large spectrum of clinical manifestations ranging from single healing to severe chronic lesions. Depending on the Leishmania species, lesions could be resistant or not to treatment. The evolution of lesions is determined by a complex interaction between parasite factors and the early immune responses triggered, including innate and adaptive mechanisms. Moreover, lesion resolution requires parasite control as well as modulation of the pathologic local inflammation responses and the initiation of wound healing responses. Here, we have summarized recent advances in understanding the immune response to cutaneous leishmaniasis: i) in North Africa caused by Leishmania (L.) major, L. tropica, and L. infantum, which caused in most cases localized autoresolutives forms, and ii) in French Guiana resulting from L. guyanensis and L. braziliensis, two of the most prevalent strains that may induce potentially mucosal forms of the disease. This review will allow a better understanding of local immune parameters, including cellular and cytokines release in the lesion, that controls infection and/or protect against the pathogenesis in New world compared to Old world CL.